Implementation of the Project Based Learning Model in the Independent Curriculum in Islamic Religious Education Learning for High School Students - Abdul Rahim; Nurul Khatimah (Institute Journal and Publication Muhammadiyah University of Buton, 2023)
This research has a number of populations. The population of this study were teachers and students of Class X 1 Senior Highschool 4 Baubau. The population of Islamic Religious Education teachers is 1 person and Student X 1 is 33 people with a total population of 34 people. Because the population of this study did not reach 100 research subjects, the entire population was the object of this research. This research is qualitative research, so in collecting data researchers used observation, interview and documentation techniques. Thus, in data analysis, researchers use qualitative analysis, namely deductive, inductive and comparative thinking. The results of this research show that: 1) the project-based learning planning model for class X 1 Senior Highschool 4 Baubau was well designed by the teacher so as to create interesting and colorful learning; 2) the project-based learning implementation model for class 3) the project-based learning evaluation model for class X 1 Senior Highschool 4 Baubau was created by the teacher using evaluation tools adapted to the learning objectives to be achieved.